Вміст флавоноїдів у Cosmos sulphureus - Andrushchenko, Olena; Levon, Volodymyr (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2021)
Flavonols, anthocyanins, and chalcones were determined during the flowering phase in two genotypes of Cosmos sulphureus (regular species and its cultivar ‘Cosmic Orang’) grown in the М.М. Gryshko National Botanical Garden in Kyiv. Inflorescences, leaves, stems, roots, and separated ray and disc florets were dried and crushed to prepare extracts following three different techniques. In particular, with 80 % (v/v) ethanol following Andreeva & Kalinkina (2000), 3.5 % HCl following Kriventsov (1982), and 0.1 N HCl following Udovenko (1988). The absorbance of flavonoids was measured at 390 nm wavelength for flavonols, 530 nm – for anthocyanins, and 364 nm – for chalcones. The highest content of flavonols was found in inflorescences of both genotypes (87.79 ± 1.64 and 87.99 ± 1.75 mg / 100 g of dry weight (DW), respectively). The content of anthocyanins was found to be ranked by overground organs: inflorescences > leaves > stems. In particular, the content of anthocyanins in the inflorescences of these two genotypes was 188.95 ± 5.20 and 177.14 ± 6.81 mg / 100 g DW, respectively. In the leaves, the content of anthocyanins was 61.32 ± 1.97 and 41.33 ± 2.27 mg / 100 g DW, respectively. In the stems, the content of anthocyanins was 31.63 ± 1.16 and 25.31 ± 0.95 mg / 100 g DW, respectively. In the roots, the anthocyanins were not detected. Among the flavonoids, the highest content, in general, was found for anthocyanins. Similarly, chalcones were also localized in overground organs only and mostly in the inflorescences (39.65 ± 1.25 and 37.93 ± 0.88 mg / 100 g DW, respectively). The content of chalcones in the leaves and stems was much lower than the content of the anthocyanins and flavonols; it significantly varied for two investigated genotypes. During the detailed investigation of the flavonoids content in different parts of the inflorescence, it was found that disc florets in both genotypes had fewer flavonoids than the ray florets.